Kepastian Hukum dalam Penerapan Teknologi Kesehatan: Perlindungan Data Pasien dan Malpraktik - Rayga Rayyan; Abdul Rahman Maulana Siregar (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The rapid development of health technology has significantly contributed to healthcare services. Technologies such as Electronic Medical Records (EMR), telemedicine, and Artificial Intelligence (AI) have improved healthcare accessibility. However, these advancements also present legal challenges, particularly regarding patient data protection and liability for medical errors (malpractice). Patients have the right to data privacy, and data breaches can have serious consequences. In Indonesia, regulations such as the Ministry of Health Regulation No. 24 of 2022 on Medical Records have been implemented to strengthen patient data security. However, legal gaps still exist, particularly concerning the responsibility of third-party technology providers. Additionally, the application of technology increases the risk of malpractice, especially in the use of AI and telemedicine, where diagnostic errors can occur. Current regulations, including Law No. 17 of 2023 on Medical Health, do not fully address liability for errors involving technology. Therefore, stronger legal certainty and more comprehensive regulations are needed to keep pace with the rapid development of health technologies.